2020
DOI: 10.2147/copd.s259601
|View full text |Cite
|
Sign up to set email alerts
|

<p>Microarray Analysis of Long Non-Coding RNAs in Lung Tissues of Patients with COPD and HOXA-AS2 Promotes HPMECs Proliferation via Notch1</p>

Abstract: Background and Objectives: Long non-coding RNAs (lncRNAs) play an important role in the pathogenesis of many diseases, including cancer, pulmonary fibrosis and chronic obstructive pulmonary disease (COPD). In this study, we intended to identify the differentially expressed lncRNAs and the role of HOXA cluster antisense RNA 2 (HOXA-AS2) in patients with COPD. Methods: We analyzed lncRNA profiles of three non-COPD and seven COPD patients' lungs via microarray and then validated the expression of the top differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
(39 reference statements)
1
12
0
Order By: Relevance
“…Based on previous study, we conducted this study. Consistent with this study, 25 the results in our study showed that serum LUCAT1 levels were increased in smokers without COPD and in patients with COPD compared with non‐smokers; simultaneously, the difference in LUCAT1 level was more significant in patients with COPD and smoker COPD group, suggesting that COPD disease status and smoking may cause elevated serum LUCAT1 levels. It is more important that the ROC analysis confirmed the potential of LUCAT1 in discriminating COPD from smokers or non‐smokers, with the AUC results of 0.5921 and 0.8923.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Based on previous study, we conducted this study. Consistent with this study, 25 the results in our study showed that serum LUCAT1 levels were increased in smokers without COPD and in patients with COPD compared with non‐smokers; simultaneously, the difference in LUCAT1 level was more significant in patients with COPD and smoker COPD group, suggesting that COPD disease status and smoking may cause elevated serum LUCAT1 levels. It is more important that the ROC analysis confirmed the potential of LUCAT1 in discriminating COPD from smokers or non‐smokers, with the AUC results of 0.5921 and 0.8923.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, Zhou et al illustrated that lncRNA LUCAT1 was significantly upregulated in tissues from COPD patients using microarray analysis. However, Zhou et al 25 did not study the underlying mechanisms of LUCAT1 in COPD development. Based on previous study, we conducted this study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, research on lncRNA may help improve the diagnosis and treatment of lung in ammatory diseases, such as COPD. Furthermore, previous studies revealed that lncRNAs differentially expressed in lung tissue from non-smokers and smokers without or with COPD [5,16]. As a relatively wellinvestigated lncRNA, CCAT1 has been demonstrated to facilitate cell proliferation and inhibit apoptosis in lung cancer [17].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs have been identi ed as essential regulators in numerous biological processes, such as cell proliferation, differentiation, apoptosis, and in ammatory response [4]. Several studies have recently shown that exposure to cigarette smoke in both humans and rats lead to global alterations in lncRNA expression [5,6], indicating the potential role of lncRNAs as a novel group of targets for the treatment of cigarette smoke-related lung diseases. Colon cancer-associated transcript 1 (CCAT1), a lncRNA of about 11 kb located on chromosome 8q24.21, was one of the rst lncRNAs that were revealed to play functional roles in the pathogenesis of different types of human cancers, including lung cancer [7].…”
Section: Introductionmentioning
confidence: 99%
“…miRNA-22-3p were lower in the BS compared to the tobacco smoking group, thus these findings would suggest a pro-inflammatory role for miR02203p [ 178 ]. Other kinds of ncRNAs, including long non-coding (lncRNAs) and circular (circRNAs) RNAs, have also been implicated in COPD pathogenesis [ 169 , 179 , 180 , 181 ]. Interestingly, we now know that ncRNAs can also affect the UPR [ 182 , 183 ].…”
Section: Chronic Obstructive Pulmonary Diseasementioning
confidence: 99%